Dancing Democracy: The Power of the Third Eye - Prakash A Raj; RAJ (Prakash A) (New Delhi Rupa & Co, 2006)
Balanced overview of politics, public uprisings in Nepal. illus. excellent introduction
Keywords: Political Parties; Maoists; Royal Nepal Army; Constituent Assembly